The medium- and long-term outcome of total shoulder arthroplasty for primary glenohumeral osteoarthritis in middle-aged patients. (July 2017) - Sowa, B.; Bochenek, M.; Bülhoff, M.; Zeifang, F.; Loew, M.; Bruckner, T.; Raiss, P.
Abstract : Aims: Promising medium-term results from total shoulder arthroplasty (TSA) have been reported for the treatment of primary osteoarthritis in young and middle-aged patients. The aim of this study was to evaluate the long-term functional and radiological outcome of TSA in the middle-aged patient. Patients and Methods: The data of all patients from the previous medium-term study were available. At a mean follow-up of 13 years (8 to 17), we reviewed 21 patients (12 men, nine women, 21 shoulders) with a mean age of 55 years (37 to 60). The Constant-Murley score (CS) with its subgroups and subjective satisfaction were measured. Radiological signs of implant loosening were analysed. Results: Two shoulders (two patients) were revised and in two shoulders of two different patients, revision surgery was recommended. The mean CS increased from 23.3 (10 to 45) pre-operatively to 56.5 (26 to 81; p < 0.0001), but with a decrease in CS from 62.8 (38 to 93) to 56.5 (26 to 81) between medium- and long-term follow-up (p = 0.01). Without revision surgery, 18 patients (95%) rated their result as good or very good. The mean radiolucent line score for the glenoid components increased from 1.8 (0 to 6) to 8.2 (2 to 18) between medium- and long-term follow-up (p < 0.001). Conclusion: TSA in young and middle-aged patients leads to improvement in clinical function and a relatively high satisfaction rate. However, clinical or radiological glenoid loosening worsens in the long term. Further studies are needed to optimise the treatment options in this patient population. Cite this article: Bone Joint J 2017;99-B:939–43.